Jejak Peradaban Timur: Pembentukan Identitas Indonesia Melalui Harmoni Budaya - Tomy Wijaya; Fatimah Alauwiyah; Devinna Nurrohma; Ayu Oktavia (Universitas PGRI Yogyakarta, 2024)
This research reveals traces of Eastern civilization in Indonesian history through qualitative analysis of historical and archaeological sources. Using qualitative research methods, this research found that Eastern civilizations such as China, India and Arabia had a significant influence on the development of culture, religion and politics in Indonesia. Data collected from primary and secondary sources shows that interactions between Eastern and Indonesian civilizations have been going on for centuries, shaping Indonesia's cultural and historical identity. This research contributes to a deeper understanding of the role of Eastern civilization in Indonesian history and its relevance to the contemporary cultural context. Keywords: Civilization, Identity, Culture.